Self image and simulation of a PR-box using high-order paraxial beams - Avalos Pinillos, Victor Andre (2019)
From Maxwell equations (for a free of charge and current, isotropic and homoge- neous medium) and the paraxial approximation, which is to suppose the beam of light moves towards a preferred direction (longitudinal propagation), we ar- rive at the paraxial wave equation, which depending of the constraints of the situation, can be solved by different type of beams. We are intersested in higher- order mode paraxial beams. If we solve the equation with cartesian coordinates, we arrive at Hermite-Gauss beams, if we solve with cilindrical coordinates, we obtain Laguerre-Gauss beams. Each of them has specific characteristics which motivated their use in the two phenomenons presented here: Self Image and the Simulation of a PR box. We call self image to the phenomenon where we are capable of replicating an initial image, over free space longitudinal propagation. What we propose here is a self image produced by the collinear and coherent interference of paraxial Laguerre Gauss (LG) beams, which constrasts with the usage of a fundamen- tal Gaussain beam in Talbot’s self image. Gouy phases, which are the key component that make this phenomenon possible, are exclusive of Higherorder paraxial beams. We show, experimentally, the phenomenon of self image using the superposition of 3 LG beams with specific mode orders.